Pendampingan Belajar Matematika Melalui Metode Jarimatika dalam Meningkatkan Kemampuan Berhitung Perkalian di Bimbel Baskara Desa Sidoharjo Kecamatan Pulung - Sunyahni Sunyahni; Medina Nur Asyifa Purnama (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research was motivated by a lack of students' skills in operating arithmetic, most of them were not fast and precise in helping to multiply numbers. Based on these problems the authors conducted research by learning arithmetic using the fingers.This study intends to improve students' multiplication numeracy skills in Baskara training, Sidoharjo Village, Pulung District. This learning assistance uses the jarimatics method. The results of this study indicate that the application of the jarimatics method can improve students' numeracy skills. Students look active and happy when applying the jarimatics method. Data collection in this study used the ABCD (Asset-based community development) data method. The test results showed that the majority of students had good multiplication arithmetic skills. In addition, there are two criteria for the effectiveness of learning methods that are fulfilled. First, the improvement and difference between initial understanding and after learning. Both can increase the interest and motivation of students who have difficulty calculating multiplication.